Intergenerational Gender Preferences in Romantic Partner Selection: An Indonesian Perspective - Octavia Regina Caeli; Karel Karsten Himawan (Interpersona: An International Journal on Personal Relationships, 2025)
Trends in the transition of gender role expectations that have occurred in the last few decades have slowly shifted the views regarding the characteristics that are deemed important in a romantic partner. Both evolutionary and contemporary perspectives are considered in the effort to better understand changes in these shifts. This study aims to explore these shifts by comparing data from two generations based on the year of marriage. Using a cross-sectional design, 279 Indonesian heterosexual married adults (Mage = 39.95; SD = 10.23) completed the Mate Preferences Questionnaire. Participants were grouped by the year of marriage: the senior group (n = 96; married before 2000) and the younger group (n = 163; married after 2000). Their responses were analyzed using a two-way ANOVA. The study results show that based on sex differences, there were no significant differences between the senior group and the younger group in romantic partner preferences. However, when considering the time of marriage, participants in the younger group prioritised certain criteria more strongly than those in the senior group. These included maintaining order, being ambitious, and having good prospects in terms of intelligence and finances. The interaction between gender differences and marital duration showed significant differences in the importance of similar education levels as well as good education and intelligence. The study highlights the impact of evolving gender role expectations on the process of selecting romantic partners.